Monitoring device for mushrooms’ ideal growth by using ESP32 microcontroller for farmers (MoDMush) / Ameer Farhan Ahmad Fuad - Ahmad Fuad, Ameer Farhan (2024)
This study aims to design a Monitoring Device for Mushrooms’ Ideal Growth by using ESP32 Microcontroller for Farmers, called MoDMush. In this project, several sensors will be utilized with the purpose of monitoring the current surrounding condition inside of the mushroom house. These measured parameters will be sent to the microcontroller, and according to the thresholds that were set for each of the sensors through the IoT interface, the ESP32 will respond to the data. Other than that, an IoT platform called Blynk is also implemented in this device. Via a stable internet connection, this platform allows users to monitor the real – time surrounding condition of the cultivation area remotely by merely installing an application in their smartphones. A DHT22 Air Temperature and Humidity Sensor, MQ – 135 Air Quality Sensor and Water will be the input, meanwhile the LCD, LED and Water Spray will be the output in this project. By integrating both hardware and software implementations, this project strives to create an advanced and efficient method of farming. This will in return help to reduce the significant amount of workload required in mushroom cultivation sector as compared to the traditional method of farming. Therefore, it can be said that this project facilitates the workload of farmers, and in conjunction with that, helps to reduce the labor cost required for the mushroom cultivation process